The effect of intensive fattening of bulls with a high-concentrate diet on ruminal mucosa – a morphometric study - Černík, Julius; Štercová, Eva; Šterc, Jan; Fictum, Petr; Luňáček, Jiří; Halouzka, Roman (University of Veterinary and Pharmaceutical Sciences in Brno, 2011)
The aim of the study was to identify the effect of fattening of experimental Simmental bulls (a total of 10 animals) with a high-concentrate diet on ruminal mucosa and dimensions of ruminal papillae, and to assess the intensity of keratinization of papillary epithelium. The experimental period lasted from weaning to slaughter (359 days). Histopathological and morphometric examinations of ruminal mucosa indicated that the ruminal papillae of bulls from the experimental group were better developed (long with a lower degree of keratinization) compared to the control group. Significant differences between the experimental and control groups were found in the length of ruminal papillae (p = 0.005), width of stratum corneum (p = 0.034) and degree of mucosal keratinization on the surface of ruminal papillae (p = 0.014). Conclusive results of morphometric analysis prove the facility of the use of morphometrics as a method useful for veterinary pathology, mainly for the accuracy of the histological diagnosis.

The aim of the study was to identify the effect of fattening of experimental Simmental bulls (a total of 10 animals) with a high-concentrate diet on ruminal mucosa and dimensions of ruminal papillae, and to assess the intensity of keratinization of papillary epithelium. The experimental period lasted from weaning to slaughter (359 days). Histopathological and morphometric examinations of ruminal mucosa indicated that the ruminal papillae of bulls from the experimental group were better developed (long with a lower degree of keratinization) compared to the control group. Significant differences between the experimental and control groups were found in the length of ruminal papillae (p = 0.005), width of stratum corneum (p = 0.034) and degree of mucosal keratinization on the surface of ruminal papillae (p = 0.014). Conclusive results of morphometric analysis prove the facility of the use of morphometrics as a method useful for veterinary pathology, mainly for the accuracy of the histological diagnosis.
The effect of intensive fattening of bulls with a high-concentrate diet on ruminal mucosa – a morphometric study
Keywords: Cattle; rumen; grain; morphometry; ruminal epithelium.; Cattle; rumen; grain; morphometry; ruminal epithelium.